Ответы и объяснения

  • Участник Знаний
2013-06-19T13:17:19+04:00

1/х+1/(х-1)=5/6

 

ОДЗ

 

x≠0

x≠1

 

1/х+1/(х-1) - 5/6 = 0

 

6(x-1)+6x-5x(x-1)=0

 

6x-6+6x-5x^2+5x=0

 

-5x^2+17x-6=0  /:(-1)

 

5x^2-17x+6=0

 

D= 289 -120 = 169 = 13^2

**************

  • Участник Знаний
2013-06-19T13:21:50+04:00

6*(1*((X-1) + 1*X) = 5*(X*(X-1))

6*(X-1+X) = 5*(X^2 - X)

12X - 6 = 5X^2 - 5X

5X^2 - 17X + 6 = 0

D = 289 - 4*5*6 = 289 - 120 = 169

V D = 13

X1 = (17 + 13) \ 10 = 3

X2 = (17 - 13) \ 10 = 0.4

Ответ: X1 = 3  ;  X2 = 0.4